Sexual Dysfunction and the Impact of Beta-Blockers in Young Males With Coronary Artery Disease - Dai, Yuxiang; Mei, Zhendong; Zhang, Shuning; Shali, Shalaimaiti; Ren, Daoyuan; Xu, Lili; Gao, Wei; Chang, Shufu; Zheng, Yan; Qian, Juying; Yao, Kang; Ge, Junbo (Frontiers in Cardiovascular Medicine, 2021)
Objective: We aimed to assess the association of erectile dysfunction (ED) with the extent of coronary atherosclerosis, and to examine whether revascularization and medication use have an impact on ED status in patients with early onset of coronary artery disease (EOCAD). Methods: International Index of Erectile Function (IIEF-5) was used to evaluate sexual function in 296 male patients with EOCAD (age, 39.9±4.8 years), and 354 male controls (age, 40.6±4.4 years). The extent of coronary atherosclerosis was measured by Gensini score. Endothelial function was evaluated by two vasomotor indexes including endothelin-1 (ET-1) and nitric oxide (NO) by ELISA. Results: ED was more frequent (57.8% vs. 31.1%, P<0.001) and serious (IIEF-5 score:17.7±6.0 vs. 21.6±5.0, P<0.001) among EOCAD patients than that among controls. IIEF-5 score was negatively correlated with Gensini score (r=−0.383, P=0.0003). The adjusted odds ratio (OR) for the presence of ED (EOCAD vs. controls) was 1.88 (95% confidential interval [CI], 1.12-3.18). However, ET-1 and NO attenuated the association between ED and EOCAD (adjusted OR: 1.54, 95% CI: 0.84-2.80). IIEF-5 score increased after coronary revascularization in patients not on beta-blockers (18.71±4.84 vs. 17.59±6.05, P<0.001) as compared with baseline, while stayed unchanged in the subgroup using beta-blockers (17.82±5.12 vs. 17.70±5.98, P=0.09). Conclusions: ED was common in patients with EOCAD, and associated with the severity of coronary atherosclerosis. Endothelial dysfunction may be a pathophysiologic mechanism underlying both ED and EOCAD. Coronary revascularization confers a benefit in ED amelioration, while this effect did not appear in patients using beta-blocker.